2015
DOI: 10.5539/elt.v8n5p33
|View full text |Cite
|
Sign up to set email alerts
|

Education Context and English Teaching and Learning in the Kingdom of Saudi Arabia: An Overview

Abstract: This paper discusses the education context and English teaching and learning in the Kingdom of Saudi Arabia (KSA). The paper is organised into five main sections. The first section offers a brief glance at the social, religious, economic, and political context in KSA. The second section provides an overview of the education system in KSA, which includes a brief explanation of the history of education, a discussion of the role of government in modern education, and a description of the administration of educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
164
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(167 citation statements)
references
References 15 publications
3
164
0
Order By: Relevance
“…A study conducted by Altwaijri (1982) revealed that the students from Saudi government schools have been studying English language since 10 years, but their performance is not satisfactory. Therefore, most of the students lack the skills and motivation of learning English language, who are admitted in university programs after passing from high schools (Alrashidi & Phan, 2015;Al-Nasser, 2015). There is an immediate need of conducting various academic projects and search for improved teaching qualities at the Saudi government schools to implement the objectives and aims of vision 2030.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted by Altwaijri (1982) revealed that the students from Saudi government schools have been studying English language since 10 years, but their performance is not satisfactory. Therefore, most of the students lack the skills and motivation of learning English language, who are admitted in university programs after passing from high schools (Alrashidi & Phan, 2015;Al-Nasser, 2015). There is an immediate need of conducting various academic projects and search for improved teaching qualities at the Saudi government schools to implement the objectives and aims of vision 2030.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The stages of schooling for both boys and girls' schools are the same, and so are the educational facilities and syllabi, albeit for "small differences to meet the needs of each gender" (Alrashidi & Phan, 2015).…”
Section: Gender and Education In Ksamentioning
confidence: 99%
“…The first public school was established in 1930, two years before the founding of present-day Saudi Arabia (Alrashidi & Phan, 2015). For the first thirty years, however, only male students were enrolled in schools.…”
Section: Gender and Education In Ksamentioning
confidence: 99%
“…Altwaijri (1982) stated that "Saudi students study English for nearly ten years, yet their overall performance level in English is low" (p. 6). For the above-mentioned reasons, the majority of students, who move from high school to university, generally lack the skills and motivation in learning and in acquiring English language, and that lack is evidenced by their low scores (Al-Nasser, 2015;Alrahaili, 2013;Alrashidi & Phan, 2015;Elyas & Picard, 2010). Thus, it was necessary to take initiatives and to conduct comprehensive academic projects for searching for the best ways and means to improve the quality of teaching and learning English at Saudi government schools.…”
Section: Literature Reviewmentioning
confidence: 99%